Design and performance of an internal-cooling turning tool with micro-channel structures. (September 2019) - Peng, Ruitao; Jiang, Haojian; Tang, Xinzi; Huang, Xiaofang; Xu, Ying; Hu, Yunbo
Abstract: The application of coolant is generally in the metal cutting process. However, conventional flood cooling shows inadequate cooling effect during the machining of superalloys. Internal-cooling approach is a capable alternative to enhance the heat transfer ability of coolant and lower the machining temperature. In this paper, an internal-cooling turning tool with micro-channel structures is proposed for turning Inconel 718. Initially, computational fluid dynamics (CFD) simulation was conducted to evaluate the micro-channel structures inside the tool. The micro-channel diameter shows a great influence on the coolant outlet velocity which appreciably affected the heat dissipation ability of the tool. According to the simulation results, the micro-channel diameter was set to 2 mm. Subsequently, various structures of the tool were machined and assembled. Finally, turning experiments of Inconel 718 were conducted under dry, flood cooling and internal-cooling conditions. Using the same turning parameters, internal-cooling technology is advantageous to offer higher heat transfer efficiency and lead to smaller cutting force, lower cutting temperature and more favorable surface topography, compared with the dry and conventional flood cooling approaches. Under internal-cooling condition, the cutting force and cutting temperature decreases gradually as the coolant inlet pressure increases. Besides, higher inlet pressure also leads to lower surface roughness.